2010
DOI: 10.1111/j.1574-695x.2010.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

The distributed genome hypothesis as a rubric for understanding evolutionin situduring chronic bacterial biofilm infectious processes

Abstract: Most chronic infectious disease processes associated with bacteria are characterized by the formation of a biofilm which provides for bacterial attachment to the host tissue or implanted medical device. The biofilm protects the bacteria from the host’s adaptive immune response, as well as predation by phagocytic cells. However, the most insidious aspect of biofilm biology from the host’s point of view is that the biofilm provides an ideal setting for bacterial horizontal gene transfer (HGT). HGT provides for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 100 publications
4
76
0
9
Order By: Relevance
“…Consistent with our findings is that 10 of 11 previously reported cases of VRSA were identified from wounds [18]. Wounds may be an important reservoir for VRSA emergence because of the propensity for biofilm formation within wounds; biofilms can enhance bacterial growth and lateral gene transfer [19].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings is that 10 of 11 previously reported cases of VRSA were identified from wounds [18]. Wounds may be an important reservoir for VRSA emergence because of the propensity for biofilm formation within wounds; biofilms can enhance bacterial growth and lateral gene transfer [19].…”
Section: Discussionsupporting
confidence: 92%
“…For insertion of IS5 into both the bgl and glpFK operons, the environment influences the mutation rate. In addition, in biofilms, some cells increase their mutation rate during stress by increasing competence during chronic infections (Ehrlich et al, 2010). Hence, these examples demonstrate a Lamarckian-type evolution (that is, environment-driven mutation) that differs from that of Darwin, which holds that mutation rates should not depend on the environment (Koonin and Wolf, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…However, wholegenome sequencing (WGS) has shown that multiple strains with the same PFGE and MLST patterns have significantly different genetic contents and these methods lack the resolution to provide strain specific diagnostics at this point 6 . Ultrasequencing or pyrosequencing has demonstrated multiple strains of HIV-1 within a single individual and identification of minority mutants in the quasi-species.…”
Section: Sequencingmentioning
confidence: 99%